Initial experience with cinematic rendering for the visualization of extracardiac anatomy in complex congenital heart defects - Röschl, Florian; Purbojo, Ariawan; Rüffer, André; Cesnjevar, Robert; Dittrich, Sven; Glöckler, Martin (Interactive Cardiovascular and Thoracic Surgery, 2019)
OBJECTIVES: Detailed anatomical information is essential for planning of surgical therapy in patients with congenital heart disease. We wanted to determine whether cinematic rendering, the novel 3-dimensional visualization technique, could help paediatric cardiac surgeons achieve better preoperative visualization of the extracardiac anatomy in patients with complex congenital heart defects. Therefore, cinematic rendering was compared to the traditional volume rendering technique by means of a questionnaire with predefined criteria. METHODS: Picture sets from 20 infant patients (mean age = 17 days) were generated from computed tomography data with both the cinematic rendering and the volume rendering techniques. These were presented side by side in a digital high-resolution portfolio without labelling them. Three experienced paediatric cardiac surgeons were provided with these portfolios and a questionnaire. They were asked to evaluate the images individually in predefined categories on a 4-point Likert scale from 1 = 'fully acceptable' to 4 = 'unacceptable'. RESULTS: Cinematic rendering scored significantly better values on the Likert scale in 7 of 9 categories, namely 'spatial impression in general', 'depth perception', 'delineation of the atrial appendages/pulmonary veins/peripheral pulmonary arteries', 'assessability of the anterior interventricular sulcus' and 'assessability of the aortic arch branches'. CONCLUSIONS: Cinematic rendering is a valuable software tool, and our data suggest that it provides significantly better visualization than volume rendering. The surgeons appraised improved depth perception and delineation of structures adjacent to the heart as the most significant advantages.
CRIS-Team Scopus Importer:2019-06-18
Keywords: Cinematic rendering; Computed tomography; Congenital heart disease; Three-dimensional